Schelling's dialogical freedom essay : provocative philosophy then and now - Freydberg, Bernard, 1947- (SUNY series in contemporary continental philosophy., 2008)
With clarity and liveliness, Bernard Freydberg explores the major themes treated in Schelling's final public work: freedom, imagination, the nature of God, indifference, and love. Freydberg also examines Schelling's engagement with philosophy's history, including the relationship between his ideas and those of Plato and Kant, his oracular and mythical languages, and his relevance to contemporary thought.